Virtue Ethics and the Trilemma Facing Sentiocentrism: Questioning Impartiality in Environmental Ethics - Rodrigues Pereira, Rafael (Environmental ethics, 2021)
This article aims to question the value of impartiality in environmental ethics by highlighting a problem internal to the bioethics approach known as sentiocentrism. The principle that all beings with the same degree of consciousness should receive the same moral treatment would lead to a trilemma, i.e., the need to choose among three morally unacceptable choices. I argue those problems are related to the premise, shared by Utilitarianism and rights-centered theories, that impartiality is the constitutive feature of the moral point of view. In the last part of my article, I discuss how this problem points to some advantages of a virtue ethics approach to environmental ethics.